Selected ion flow tube studies of the reactions of H3O+, NO+, O2+˙ and O-˙ ions with alkanes in He and N2 carrier gases at different temperatures - Omezzine Gnioua, Maroua; Swift, Stefan J; Španěl, Patrik (Physical chemistry chemical physics, 2024)
The kinetics of the reactions of H3O+, NO+, O2+˙ and O-˙ with n-hexane, 3-methylpentane, 2,5-dimethylhexane and 2,3-dimethylheptane were studied experimentally under several selected ion flow tube (SIFT) conditions: in a Profile 3 instrument in He and N2 carrier gases at 300 K and in the Voice200 instrument in N2 carrier gas at 300 and 393 K - where the effect of the extraction lens voltage was also assessed. It was found that H3O+ ions react differently than expected, with reaction rates slower than collisional. Instead of transferring a proton, they associate and form fragment product ions [M-H]+. NO+ ions react via hydride ion transfer. O2+˙ ions react via charge transfer followed by fragmentation that is highly sensitive to the temperature and the ion extraction lens voltage. Negative ions did not react, except for the O-˙ ion, which reacted via an associative detachment process. Computational analysis using Density Functional Theory (DFT) provided insights into the exothermicities and exergodicities of these reactions. A notable result is that proton transfer from H3O+ does not take place despite its potential exothermicity; this is important for the interpretation of proton transfer reaction (PTR) and SIFT mass spectrometry data.